Potential of Energy Efficiency and Conservation Measures in Residential Buildings in Ghana (Case Study of Student Hostel) - Sufyan, Yakubu; Anuware, Sadat Abdulai; Mathias, Maclar; Francis, Atta Kuranchie; Talib, Paskwali Beshir Latio; Nyagong, Santino David Ladu (Journal of Energy Conservation, 2024)
Promoting responsible energy usage in student hostels and residential buildings plays a crucial role in ensuring sustainable development. By implementing cost-efficient strategies for managing and conserving energy, both students and homeowners can not only reap economic and social benefits but also mitigate the adverse environmental effects associated with energy consumption. Unfortunately, student hostels and residential buildings in developing countries like Ghana are falling behind in the adoption of energy efficiency and management practices, thereby missing out on valuable implementation opportunities. This study investigates the potential for energy efficiency and conservation measures in student hostels, specifically the GETFUND hostel of the University of Energy and Natural Resources in Ghana. The hostel's monthly energy consumption is approximately 64,929.458kWh, which translates to $5,667.20. The objectives of the study include analysing the current electricity consumption pattern, identifying energy misuse, and recommending measures to save energy, as well as calculating the financial benefits of implementing energy management practices. The methodology employed is an energy audit approach. The results of this study can contribute to overall energy conservation efforts in Ghana and may be applied to other university residence halls in sub-Saharan African countries with similar climatic and energy-use characteristics. In a broader sense, the primary objective of this study is to enhance the energy efficiency of the GETFUND hostel and minimize energy wastage, resulting in substantial financial savings.
Keywords: Energy efficiency and Conservation; Energy audit; University of Energy and Natural Resources; Energy management program; Residential Energy consumption; Ghana